INOVASI PEMBELAJARAN BAHASA ARAB: INTEGRASI COLLABORATIVE LEARNING MELALUI TEKS DRAMA DALAM BUKU TEKS MUTHALA'AH (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study addresses the problem of teacher-centered and conventional Muthala’ah learning at MTs Assalam Lahat, where students remain passive and encounter difficulties in comprehending Arabic texts. The research aims to develop and evaluate an innovative Arabic reading material integrating Collaborative Learning through drama texts to enhance students’ comprehension and engagement. Using a Research and Development (R&D) approach adapted from the simplified Borg & Gall model, the study was conducted through six stages: needs analysis, data collection, product design, expert validation, revision, and try-out. Data were collected through interviews, observations, questionnaires, documentation, and pre-test–post-test assessments. Expert validation indicated high feasibility with a score of 88% from both material and media experts. The product try-out involving eighth-grade students demonstrated significant improvement in learning outcomes, as shown by the increase in the mean score from 46.53 (pre-test) to 86.11 (post-test). A Paired Sample T-Test confirmed a significant difference (sig. 0.000 < 0.05), while the N-Gain score of 0.7437 indicated high effectiveness. The findings conclude that integrating Collaborative Learning and drama texts is effective in improving students’ reading comprehension, interaction, and motivation, making the developed material feasible and beneficial for Arabic language learning.